ADVANTAGES AND DISADVANTAGES OF STUDYING ENGLISH NON-FORMALLY BY SCHOOL STUDENTS - Lukas LepeÅ¡keviÄius; Rima JasnauskaitÄ— (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose, 2016)
The article deals with the educational situation when students of the school of general education start studying English as a foreign language additionally, i.e. non-formally. Though English is a compulsory subject in their school curriculum, they subject themselves to two types of difficulties: the doubled learning load, learning time and number of assignments as well as unusual, peculiar and unaccustomed teaching/learning process or environment. The peculiarity of non-formal learning process is characterised by some specific features such as: peculiar environment; active participation; the method of learning from experience; open and informal communication; creation of non-competitive environment; application of a number of principles such as the principle of relevance, democracy, accessibility, individualization and the principle of free will. The problem of the research is what positive and negative aspects of non-formal studying of English as a foreign language are according to the experience of school students. The aim is to find out the advantages and disadvantages of non-formal learning of English as the form of additional studying. The methods applied in the research: the analysis of theoretical sources; the interview (semi-structured) and content analysis. The participants of the research: five school students who learn English non-formally after school. The analysis of the results gained during the qualitative research proved the following: the advantages of non-formal English language learning comprises the following aspects according to the answers of the interview participants: (1) attractiveness of the activity, (2) safe learning environment, (3) individual teaching, (4) increased self-esteem, (5) effectiveness of the activity, (6) benefits of non-formal learning. The disadvantages of the non-formal English language learning comprise the following aspects: (1) lack of time (double workload, lots of homework, long sessions); (2) psychological tension; (3) unusual surroundings; (4) problems with non-formal time-table; (5) expensive activity (expensive teaching and expensive learning); (6) failure to satisfy individual demands. The amount of interview data referring to the advantages and disadvantages of non-formal learning of English revealed the fact that the interviewees were more at ease speaking about benefits than losses of this way of studying; consequently, they posses more positive than negative experience in learning English after school non-formally.